GAMBARAN PENGETAHUAN PASIEN HIPERTENSI DALAM MENGKONSUMSI OBAT TRADISIONAL DI UPT PSTW KHUSNUL KHOTIMAH PEKANBARU - Lora Marlita (Jurnal Keperawatan Abdurrab, 2016)
World Health Organization (WHO) said 65% of the population of developed countries have used traditional medicine. Traditional medicine is a treatment that uses the media content of plants with natural materials as raw materials. One example of traditional medicine to treat hypertension is garlic (allium sativum), garlic contains potassium, an important electrolyte potassium is needed by the body to maintain balance blood pressure. Excess use of traditional medicine is a traditional herb cheaper price, mduah obtained and treatment was also not complicated potion. The purpose of this study was to determine Overview Knowledge Hypertension In Patients Taking Traditional Medicines in Social Care Unit ELDERLY Khusnul Khotimah Pekanbaru in 2013. This type of research is a quantitative descriptive design (simple descriptive), the whole population of hypertensive patients totaling 38 people, with a sample of 38 people. Sampling techniques in this study is total sampling. Data collection is done by asking the Premier directly to the respondent. Data analysis performed univariate. From the research that has been carried out it was concluded that the respondents' knowledge about traditional medicine for hypertension in particular generally good garlic that is 22 respondents (57.9%), respondents who had received information are 32 respondents (84.2%), and respondents who received information through counseling by 20 respondents (62.5%). Conclusions from the results of research condukted in Pekanbaru Khotimah Khusnul PSTW UPT 2013 is a good knowledge of the respondent. Expected from the research community, especially patients with hypertension in order to know and apply the traditional drugs